2022
DOI: 10.1038/s41598-022-06396-0
|View full text |Cite
|
Sign up to set email alerts
|

Using citizen science to test for acoustic niche partitioning in frogs

Abstract: The acoustic niche hypothesis proposes that to avoid interference with breeding signals, vocal species should evolve to partition acoustic space, minimising similarity with co-occurring signals. Tests of the acoustic niche hypothesis are typically conducted using a single assemblage, with mixed outcomes, but if the process is evolutionarily important, a pattern of reduced acoustic competition should emerge, on average, over many communities. Using a continental-scale dataset derived from audio recordings colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 50 publications
2
5
0
Order By: Relevance
“…However, artificial intelligence still largely lacks the possibility to inform the operator about the diagnostic traits to differentiate between species (Wäldchen & Mäder, 2018), and thus can have limited relevance for more traditional taxonomic studies relying on sets of explicit diagnostic characters. Our results also add to the increasing evidence highlighting the invaluable role of data collected by citizen scientists in contributing to understand species' distributions and ecology, as well as for fostering species' conservation at different spatial scales (Allen‐Ankins & Schwarzkopf, 2022; Wang Wei et al., 2016). To our best knowledge, this is the first case study to apply a quantitative photography‐based identification method for discriminating phenotypically highly similar species from citizen‐science records, thus representing an effective and repeatable framework to disentangle the distributions of poorly studied species.…”
Section: Discussionsupporting
confidence: 65%
“…However, artificial intelligence still largely lacks the possibility to inform the operator about the diagnostic traits to differentiate between species (Wäldchen & Mäder, 2018), and thus can have limited relevance for more traditional taxonomic studies relying on sets of explicit diagnostic characters. Our results also add to the increasing evidence highlighting the invaluable role of data collected by citizen scientists in contributing to understand species' distributions and ecology, as well as for fostering species' conservation at different spatial scales (Allen‐Ankins & Schwarzkopf, 2022; Wang Wei et al., 2016). To our best knowledge, this is the first case study to apply a quantitative photography‐based identification method for discriminating phenotypically highly similar species from citizen‐science records, thus representing an effective and repeatable framework to disentangle the distributions of poorly studied species.…”
Section: Discussionsupporting
confidence: 65%
“…However, the calling site separation among these bush frogs is similar to the calling site preference of other taxa such as cicadas (Sueur 2002) and crickets (Diwakar & Balakrishnan 2007). Although such call stratification is known from some frog communities in the Americas and Europe (Hödl 1977, Lamb 1987, Ptacek 1992, Amézquita et al 2011, Nityananda & Bee 2011, Bignotte-Giró et al 2019, Allen-Ankins & Schwarzkopf 2022, to the best of our knowledge, this is the first evidence from an amphibian community in Asia.…”
Section: Discussionsupporting
confidence: 58%
“…2011, Nityananda & Bee 2011, Bignotte-Giró et al . 2019, Allen-Ankins & Schwarzkopf 2022), to the best of our knowledge, this is the first evidence from an amphibian community in Asia.…”
Section: Discussionmentioning
confidence: 73%
“…Previous studies have found that some birds can change the frequency of their calls (Slabbekoorn & Peet, 2003) while others can time their calls to fill the spaces between noise (Brumm, 2006; Ficken et al, 1974) to avoid frequency or temporal acoustic overlap. In addition, the overlap in the frequency bandwidth of vocalizations made by sympatric frog species was less than predicted by chance, providing evidence of an acoustic niche (Allen‐Ankins & Schwarzkopf, 2022). However, there has been conflicting support for the Acoustic Niche Hypothesis as one study found synchronized vocal behavior across 10 min bins in multiple Brazilian songbirds (Kleyn et al, 2021).…”
Section: Introductionmentioning
confidence: 99%